Major Stressful Life Events and Risk of Developing Lung Cancer: A Case-Control Study. (April 2019) - Jafri, Syed H; Ali, Faisal; Mollaeian, Arash; Mojiz Hasan, Syed; Hussain, Rahat; Akkanti, Bindu; Williams, Jessica; Shoukier, Mahran; el-Osta, Hazem
Background: Lung cancer is the leading cause of cancer-related mortality and is strongly linked with smoking. We sought to determine whether major stressful life events (e.g. divorce) are also a risk factor for developing lung cancers. Methods: We performed a matched case-control study. Cases (CA) were lung cancer patients diagnosed within the previous 12 months. Controls (CO) were patients without a prior history of malignancy. Data on major stressful life events were collected using the modified Holmes-Rahe stress scale. The primary endpoint was the odds of having a major stressful life event between CA and CO. A sample of 360 patients (CA = 120, CO = 240) was needed to achieve 80% power to detect an odds ratio (OR) of 2.00 versus the alternative of equal odds using χ 2  = 0.05. Results: Between May 2015 and December 2016, we enrolled 301 patients (CA = 102, CO = 199), matched for median age (CA = 64.4 years, CO = 63.9 years), sex (CA-Male = 48%, CO-Male = 49.2%), and smoking status (ever smoker, CA = 84%, CO = 85%). There was no difference in lifetime stressful life event rate between CA and CO (95% vs 93.9%; P  = .68). However, CA were significantly more likely to have had a stressful event within the preceding 5 years than CO (CA = 77.4% vs CO = 65.8%; P  = .03, OR = 1.78). β-blocker use was significantly higher among CO (CA = 29.4%, CO = 49.7%; P  = .0007, OR = 0.42), suggesting a protective effect. Conclusion: Patients with lung cancer are significantly more likely to have had a major stressful life event within the preceding 5 years. In addition, use of β-blockers may be protective against lung cancer.